(212) The Development and Present Structure of The National Economic Accounts in The U.A.R تطوير الهيكل الحالي للحسابات الاقتصادية الوطنية في الجمهورية العربية المتحدة (U.A.R.) - Sharaf, Hussein A. (INP, 2025)
The study examines the conceptual and practical framework of national accounting as a fundamental tool for measuring and analyzing economic activity and supporting economic planning and policymaking. It begins with an introduction that highlights the importance of national income accounts in providing a comprehensive statistical framework for assessing economic performance. The study then discusses the components of the national income accounts and the methodologies employed in their compilation. It proceeds to analyze national accounting data with the aim of interpreting key economic indicators and explaining the relationships among different sectors of the economy, emphasizing the use of such data in evaluating economic performance. In addition, the study explores commodity balances and input–output tables as analytical instruments for measuring commodity flows and examining intersectoral production linkages. It also presents financial tables that illustrate the flow of financial resources within the economy. Furthermore, the study addresses the role of national budgeting in supporting economic planning and resource allocation, followed by a discussion of microeconomic accounting principles and their relationship with the broader framework of national accounting, thereby demonstrating the integration of microeconomic and macroeconomic analysis. The study also examines income and transfer transactions and their implications for income distribution and the movement of resources across economic sectors. It concludes with a set of statistical tables that support the analyses presented and provide valuable reference data for researchers and policymakers. Overall, the structure of the study indicates that it offers a comprehensive overview of the concepts, analytical tools, and practical applications of national accounting, while highlighting its significance in developing economic databases, supporting development planning, analyzing economic relationships, and providing the information required to evaluate economic performance and formulate effective public policies.